The role and place of contemporary physiotherapy in surgical patients treatment - Trojan, Grzegorz; Jaźwa, Paweł; Kultys, Jacek (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: center; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Surgery which is performed on the abdominal cavity, the thorax, the skull or the skeleton usually the one with anaesthesia is burdened with the risk of surgical complications and it disturbs physiological functions of the system considerably. The aim of the paper is to present some views on applying modern methods of physiotherapy in surgical specialties. The authors of the article have paid special attention, to the actions which prevent the heart-vascular and respiratory complications. Also stress the importance of early intestinal nourishment of the patients who were operated on. Lowering catabolism in the period following the operation reduces regulating complications of the system and accelerates the healing of the injured tissues. The process of physiotherapy in surgery wards should be subdivided into two period: the pre – operation, and the post – operation period. In the pre – operation period we introduce respiratory exercise, diaphgram exercises as well as interrib exercise and exercise for the stomach. In addition, massage of the chest accompanied by exercise improving fitness can be applied. In the post – operation pe- 72 riod, apart from the continuation of the methods used during the first period, we start teaching of an effective cough, systematic exercise of the lower limbs witch are aimed at preventing stagnation of the venous blood, inhalation, lymphatic drainage and different kinds of pressure therapy. The main aim of this period of physiotherapy is: to put the patient in an upward position as quickly as possible which leads to improvement of multi-organ efficiency, introduction of early intestinal nourishment to supply the system with the enough quantity of energy, to keep the right structure and function of mucous membrane of the small and large intestines.